ANALISIS RESPON MAHASISWA TERHADAP PENGGUNAAN APLIKASI HSK EXAM DALAM PEMBELAJARAN BAHASA MANDARIN PADA MATAKULIAH PERSIAPAN HSK 4: ANALYSIS OF STUDENTS' RESPONSES TOWARDS THE USE OF THE HSK EXAM APPLICATION IN LEARNING MANDARIN IN THE HSK 4 PREPARATION COURSE - Aiga Ventivani; Albert Jefferson Halim (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to describe the responses of students in the Mandarin Language Education Study Program at Universitas Negeri Malang regarding the use of the HSK Exam application in the HSK 4 Preparation Course. The study employs a qualitative descriptive approach, involving 48 students as research participants. The supporting instrument used to collect data was an open-ended questionnaire. The findings reveal that students responded positively to the use of the application. This is reflected in their views, which indicate that the HSK Exam application is highly beneficial for the learning process, offers a variety of engaging features, and provides comprehensive practice questions that align with the HSK 4 Exam standards. Therefore, this application can serve as an alternative learning medium for HSK material, both for classroom use and independent study.